Noção de simetria na cosmologia de Anaximandro de Mileto - Freire, João Batista (2016)
Through the philosophical movements in Ionia and through researches made on phýsis (started by the first wise men in Miletus), we elected Anaximander‟s cosmology as a fertile ground for exploring the Greek notion of symmetry. From a geographical perspective, initially, the Greeks‟ originality towards the notion of a due measure will be questioned, since the astrological and mathematical knowledge were common in Babylon and Egypt. Although the cultural environment on the Milesian commercial ports and its architecture show evidences of a possible eastern impact on the Greek thought, it will be noted (from fragments validated by the Doxography tradition) that the problem with the birthplace of the notion of harmony and of due measure is something specific of the Greek culture and inherent to its remote religiosity. The resumption of these notions refers to the issue of arché and to its divinity assumed by Thales, Anaximander and Anaximenes. The divine was not an extrinsic notion to the Milesian thought towards the first element. Therefore, we will have as a result of this investigation some assumptions for which the notion of symmetry in Anaximander, stated in his ápeiron, could be, from the dialogue between philosophy and Orphism, an assimilation of the One, as witnessed in the Derveni papyrus.